Professional development of 1st cycle: basic education teachers: contribution of participating in a continuous programme of mathematics training - Martins, Cristina (2008)
In this investigation, my aim is to study the professional development of 1st cycle teachers in the context of the Program for Continuous Education in Mathematics for 1st Cycle of Basic Education Teachers program. Knowing that, on the one hand, professional development involves a number of dimensions and that, on the other, the context of the performance has particular characteristics, namely the kind of sessions foreseen and the form of evaluation, I have devised the following questions for investigation: ─ How does the professional development of the teacher take place through participating in the training program? ─ Which is the contribution of the portfolio usage in the training program towards the professional development of the teacher?